Barriers Involve in the Energy Efficiency in the Manufacturing Industries of Pakistan - Zafar, Sohaib Sharif; Fiaz, Muhammad; Ikram, Amir; Khan, Kanwal Iqbal; Qamar, Umaima Mehmood (International Journal of Energy Economics and Policy, 2021)
The industrial sector is consuming 35% of the total energy production in Pakistan. Furthermore, many emphases are given in this domain during the past few decades. Energy crises have incredibly influenced the industrial sector which affects the country’s economy directly. Electricity saving is possible in the industrial sector by using techniques of energy management (EM). By using this technique, we can save enough energy that will offer financial and conservational help in upcoming. We cannot accomplish energy efficiency due to numerous blockades that we see in industries on regular basis. Few pieces of research have observed the barriers that impact the EE. Here is a lack of emphasis on the necessities for energy efficiency and suitable administration. The clear purpose of this study identifies the barriers that create the problem in the improvement of energy efficiency in manufacturing industries. We collected information about the barriers from various small and large industries through Interviews and research articles. We collected the data by the questionnaire technique by using a 5 Likert scale. And these responses were collected from energy representative. The outcome of this study identifies a significant relationship is existing between technical skills, poor information regarding energy management and inappropriate technology with energy efficiency improvement. There are partial mediation, training, and education that show a mediating effect between Lack of technical skills and energy efficiency improvement. Therefore, future research might be investigated other possible mediation factors in energy efficiency improvement. Keywords: Energy Efficiency, Improvement in Energy Efficiency, Barriers to energy Efficiency JEL Classifications: N75 DOI: https://doi.org/10.32479/ijeep.7599